2014
DOI: 10.1002/ange.201407359
|View full text |Cite
|
Sign up to set email alerts
|

π Aromaticity and Three‐Dimensional Aromaticity: Two sides of the Same Coin?

Abstract: A bridge between classical organic polycyclic aromatic hydrocarbons (PAH) and closo borohydride clusters is established by showing that they share a common origin regulated by the number of valence electrons in an electronic confined space. Application of the proposed electronic confined space analogy (ECSA) method to archetypal PAHs leads to the conclusion that the 4n+2 Wade–Mingos rule for three‐dimensional closo boranes is equivalent to the (4n+2)π Hückel rule for two‐dimensional PAHs. More importantly, use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(35 citation statements)
references
References 49 publications
(27 reference statements)
0
35
0
Order By: Relevance
“…[8][9][10][11][12][13][14][15] The enhanced thermodynamic stability of aromatic hydrocarbons inspired chemists to extend the aromaticity concept to inorganic chemistry with the aim of helping to rationalize, predict and synthesize stable compounds. [16][17][18][19] A simple protocol used by scientists to theoretically design inorganic aromatic compounds is the following: to build valence isoelectronic compounds to match their aromatic organic counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15] The enhanced thermodynamic stability of aromatic hydrocarbons inspired chemists to extend the aromaticity concept to inorganic chemistry with the aim of helping to rationalize, predict and synthesize stable compounds. [16][17][18][19] A simple protocol used by scientists to theoretically design inorganic aromatic compounds is the following: to build valence isoelectronic compounds to match their aromatic organic counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly,T iznado and co-workers [4] theoretically investigated the Li 6 (BH) 5 and Li 7 (BH) 5 + clusters, and discovered that the B 5 H 5 6À kernels in the global minimaa re the transmutated analogues of cyclopentadienide (C 5 H 5 À ). Solµ,T eixidor and coworkers [5] examined the intrinsic relationship between the Wade-Mingosr ule and (4n + 2) p Hückel rule using the electronic confined space analogy( ECSA)m ethod, in whicht he electronic transmutationc oncept turned out to be ak ey factor.…”
Section: àmentioning
confidence: 97%
“…After the proposal of the ET concept, ap lethora of successful examples, including the transmutation of Groups 13, 14, and 15 elements into Group 14,15, and 16 elements, have been reported. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] In this Minireview,w ewill summarize these exam-ples on both the theoretical and experimental fronts, and outlook for wider applicationsa nd future research directions of this new concept.…”
Section: Introductionmentioning
confidence: 99%
“…Carboranes have enhanced properties such as high symmetry along the C–C axis, high thermal and chemical stability, and three‐dimensional aromaticity. [4d], There are two kinds of carborane cage linkers: 10‐vertex (C 2 B 8 H 10 ) and 12‐vertex (C 2 B 10 H 12 ). Low and co‐workers showed that 10‐vertex carborane cages exhibit better electronic communication between metal centers over their 12‐vertex counterparts .…”
Section: Introductionmentioning
confidence: 99%